2005
DOI: 10.1507/endocrj.52.499
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsense Mutation in the Arg345 of the Insulin Receptor Gene in a Japanese Type A Insulin-resistant Patient

Abstract: Abstract. Defects in insulin receptor function have been associated with insulin resistant states such as obesity and type 2 diabetes mellitus. Several types of mutations in the insulin receptor gene have been identified in patients with genetic syndromes of extreme insulin resistance. We have studied a 10-year-old Japanese girl with type A insulin resistance with hirsutism and hyperinsulinemia but without the dysmorphic features characteristic of leprechaunism or RabsonMendenhall syndrome. Despite the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At 19p13.3, rs2059807 is located in the intron of the INSR (insulin receptor) gene and in previous studies, common SNPs in the INSR gene have been reported to be associated with PCOS in both Han Chinese individuals and those of European ancestry. INSR has an important role in insulin metabolism, consistent with a very common explanation for the pathogenesis of PCOS, namely, insulin resistance (8). Mutations affecting the tyrosine kinase domain of the insulin receptor are known to cause severe hyperinsulinemia and insulin resistance (9).…”
Section: Introductionmentioning
confidence: 55%
“…At 19p13.3, rs2059807 is located in the intron of the INSR (insulin receptor) gene and in previous studies, common SNPs in the INSR gene have been reported to be associated with PCOS in both Han Chinese individuals and those of European ancestry. INSR has an important role in insulin metabolism, consistent with a very common explanation for the pathogenesis of PCOS, namely, insulin resistance (8). Mutations affecting the tyrosine kinase domain of the insulin receptor are known to cause severe hyperinsulinemia and insulin resistance (9).…”
Section: Introductionmentioning
confidence: 55%
“…There are several mutations in the INSR, which have been classified into several classes: class1 (impaired receptor biosynthesis); class II (receptors with impaired processing and trafficking to plasma membrane); class III (decreased affinity to insulin binding); class IV (receptors with defective phosphorylation and kinase activity); and class V (receptor recycling defects and receptor degradation in lysosome) [61]. There are two types of INSR mutations, autosomal recessive and mild type mutations.…”
Section: Mutations In Insr and Insulin Signaling Genesmentioning
confidence: 99%
“…2,[5][6][7] Mutations in the INSR gene are the most common cause of monogenic insulin resistance, and more than 90 different mutations have been identified so far in patients with type A insulin resistance, Rabson-Mendenhall syndrome or Donohue syndrome (leprechaunism). 2,[8][9][10][11][12][13] The clinical spectrum of these inherited disorders reflects the severity of dysfunctional receptor, 12 ranging from mild type A insulin resistance to the most severe form of the disease, Donohue syndrome, which is characterized by excessive hyperglycaemia with hyperinsulinism, pre-and postnatal growth retardation, distinct dysmorphism, acanthosis nigricans and death in the first 2 years of life. Patients with Rabson-Mendenhall syndrome have a less severe phenotype but seldom survive through childhood owing to b-cell failure and severe diabetic ketoacidosis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, inherited severe insulin resistance is frequently associated with rare monogenic disorders and usually results from mutations in the insulin signalling pathway 2,5–7 . Mutations in the INSR gene are the most common cause of monogenic insulin resistance, and more than 90 different mutations have been identified so far in patients with type A insulin resistance, Rabson–Mendenhall syndrome or Donohue syndrome (leprechaunism) 2,8–13 . The clinical spectrum of these inherited disorders reflects the severity of dysfunctional receptor, 12 ranging from mild type A insulin resistance to the most severe form of the disease, Donohue syndrome, which is characterized by excessive hyperglycaemia with hyperinsulinism, pre‐ and postnatal growth retardation, distinct dysmorphism, acanthosis nigricans and death in the first 2 years of life.…”
Section: Introductionmentioning
confidence: 99%